Discovery of ∼9000 new RR Lyrae in the southern Catalina surveys. Issue 3 (24th November 2014) - Torrealba, G.; Catelan, M.; Drake, A. J.; Djorgovski, S. G.; McNaught, R. H.; Belokurov, V.; Koposov, S.; Graham, M. J.; Mahabal, A.; Larson, S.; Christensen, E.
Abstract: We present the results of a deep, wide-area variability survey in the Southern hemisphere, the first of its kind. As part of the Catalina Sky Surveys, the Siding Spring Survey (SSS) has covered 14 800 deg 2 in the declination range of −75° ≤ δ ≤ −15°. To mine the enormous SSS data set efficiently, we have developed two algorithms: automatic period selection (APS) and automatic Fourier decomposition (AFD), which aim to sharpen the period estimation and produce robust light-curve models. Armed with the APS and AFD outputs, we classify 10 540 ab-type RR Lyrae (RRab) stars (∼90 per cent of which are new) across the southern sky. As well as the positional information we supply photometric metallicities, and unreddened distances. For the RRab stars in the halo, a study of the photometric metallicity distribution reveals a nearly Gaussian shape with a mean metallicity of [Fe/H] = −1.4 dex and a dispersion of 0.3 dex. A spatial study of the RRab metallicities shows no significant radial gradient in the first ∼7 kpc from the Galaxy centre. However, further out, a small negative gradient is clearly present. This is complemented by a very obvious correlation of the mean RR Lyrae metallicity with distance above the Galactic plane, z . We have also carried out an initial sub-structure search using the discovered RRab, and present the properties of the candidates with significance greater than 2σ. Most prominent among these is a southern extension of the Sagittarius dwarf galaxy's stream system, reaching down to declinations ∼ -40 °.